Implementasi Model Waterfall Pada Sistem Informasi Pengiriman Barang Berbasis Web - Susafaati Susafaati (Universitas Bina Sarana Informatika, 2019)
Abstract— Shipping goods systems is still done manually, from serving customers until data storage which related to shipping process of making a report, so errors in registration, less accurate and delay report of required data is occurs. information system design is the best solution to solve the existing of shipping goods, as well as with the computerized system which is effective and efficient to support activities on the Web shipping item. Keywords: shipping goods system, Web.